From Fragmentation to Integration: The Challenges of Sustainable Peatland Governance - Zulkarnaini, Zulkarnaini; Asfar, Ali; Yunus, Wan Muhammad; Suandy, Indra (Jurnal Kebijakan Publik, 2025)
Sustainable peatland management requires a governance framework that can address institutional fragmentation and cross-sectoral tensions, particularly in ecologically sensitive and economically strategic coastal peatlands. Riau Province, as one of the regions with the largest coastal peatlands in Indonesia, represents the complexity of such governance due to overlapping authorities, conflicting land use interests, and pressures from natural resource-based develop-ment. This article examines the challenges of Riau's coastal peatland governance through the lens of governance frameworks and institutional analysis, with the aim of conceptualizing a shift from sectoral management to an integrated governance model. The study adopts a qualitative approach based on policy and institutional analysis, utilizing the concepts of multi-level governance, institutional interplay, and policy coherence to assess how the configuration of actors, rules, and power relations shapes peat management practices at the national and regional levels. Analytical findings indicate that governance fragmentation—reflected in inconsistent regulations, overlapping institutional mandates, and weak vertical and horizontal coordination—is a major obstacle to the sustainability of Riau's coastal peat ecosystem. This article argues that the failure of peatland governance in Riau is not merely technical-ecological in nature, but rather rooted in institutional design and the political dynamics of policy.